2022
DOI: 10.1186/s12889-022-14608-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 booster vaccine willingness among migrants from the Eastern Mediterranean living in Australia: a cross-sectional study

Abstract: Background Migrants have been disproportionally affected by COVID-19 in Australia. Vaccination against COVID-19 is a key pillar of Australia's public health response, but little is known about the willingness to receive booster vaccinations among migrants. This study aimed to assess the factors associated with a willingness to receive a COVID-19 booster vaccine among migrants living in Australia born in the World Health Organization’s Eastern Mediterranean Region (EMRO). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
4
17
0
Order By: Relevance
“…In a Malaysian study (n = 1010), lower VBH was associated with younger age, higher income, Chinese ethnicity, and fewer previous experiences of side effects [ 54 ]. Knowledge about and confidence in COVID-19 vaccines and trust in the government diminishes VBH among middle-eastern migrants in Australia [ 55 ]. Reports from culturally diverse communities suggest the need for deploying tailored interventions that address separate, context-specific VBH determinants.…”
Section: Discussionmentioning
confidence: 99%
“…In a Malaysian study (n = 1010), lower VBH was associated with younger age, higher income, Chinese ethnicity, and fewer previous experiences of side effects [ 54 ]. Knowledge about and confidence in COVID-19 vaccines and trust in the government diminishes VBH among middle-eastern migrants in Australia [ 55 ]. Reports from culturally diverse communities suggest the need for deploying tailored interventions that address separate, context-specific VBH determinants.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only 76.2% of the participants were willing to receive the booster dose of COVID-19 vaccine, which was relatively lower than other studies. 7 , 8 This might be explained by the relatively young population that we included in our study, and younger age was associated with lower willingness to receive the booster dose.…”
Section: Discussionmentioning
confidence: 91%
“…Most common sociodemographic factors associated with COVID-19 acceptance were gender, age, level of education, and marital status (Table 4). Female gender (11-21), younger age (14, 15, 17, 22-29), lower level of education (12, 16, 17, 19, 20, 22, 26, 30-32), and being single (11, 13, 26) were associated with lower vaccine acceptance in most studies.…”
Section: Methodsmentioning
confidence: 88%
“…Being concerned about vaccine development was positively associated with vaccine hesitancy in all three studies evaluating this association. Additionally, six studies examined the participants’ knowledge/attitude scores towards COVID-19 vaccines (15, 22, 24, 34, 36, 38). Two studies showed that people with greater knowledge of COVID-19 vaccines had higher intention to get vaccinated (15, 22).…”
Section: Methodsmentioning
confidence: 99%